A Data-Deriven Model for Forensic Policy Making in Electronic Banking Using Agent-Based Simulation - Khodamoradi, Afshin; Pourebrahimi, Alireza; Afshar kazemi, Mohammad Ali (Management Strategies and Engineering Sciences, 2025)
The rapid growth and expansion of information and communication technology has brought about a revolution in various aspects of human life and organizational performance. Every new technology, in order to become widespread and develop, requires legal acceptance before its full potential can be utilized. In a world where we are increasingly dependent on the virtual space and store our sensitive information on cloud and online platforms, the existence of criminals aiming to obtain this information is an undeniable and self-evident reality. With the expansion of the internet, an old topic that existed even before the advent of the internet entered the digital world. This topic is referred to as forensic science. Therefore, the main objective of this research is to propose a grounded data model for criminology policy-making in electronic banking using agent-based simulation. After presenting the model, simulators, especially Matlab, will be used according to the project's requirements, and the results will be evaluated based on execution speed. The study will continue by creating several simulations to analyze the system, with detailed results and related graphs provided. After extracting features and applying algorithms, the proposed method will be evaluated through accuracy measures.